Stimulation of cholesteryl ester synthesis in mouse peritoneal macrophages by cholesterol-rich very low density lipoproteins from the Watanabe heritable hyperlipidemic rabbit, an animal model of familial hypercholesterolemia. - Kita, T (1986)
Cholesterol-rich very low density lipoproteins (VLDL) from the homozygous Watanabe heritable hyperlipidemic (WHHL) rabbit induced marked cholesteryl ester accumulation in mouse peritoneal macrophages. This WHHL rabbit, an animal model of human familial hypercholesterolemia, has severe hypercholesterolemia, cutaneous xanthomas, and fulminant atherosclerosis due to the deficiency of the low density lipoprotein (LDL) receptor. When incubated with mouse peritoneal macrophages, the VLDL from WHHL rabbit (WHHL-VLDL) stimulated cholesteryl [14C]oleate synthesis 124-fold more than did VLDL from the normal Japanese White rabbit (control-VLDL). The enhancement in cholesteryl ester synthesis and accumulation of WHHL-VLDL was due to the presence of a high affinity binding receptor site on the macrophage cell surface that mediated the uptake and lysosomal degradation of WHHL-VLDL. Competition studies showed that the uptake and degradation of 125I-WHHL-VLDL was inhibited by unlabeled excess WHHL-VLDL and beta-migrating VLDL (beta-VLDL), but not LDL. Furthermore, the degradation of WHHL-VLDL was not blocked by either fucoidin, polyinosinic acid, or polyguanylic acid, potent inhibitors of the acetylated (acetyl)-LDL binding site, or by acetyl-LDL. These results suggest that macrophages possess a high affinity receptor that recognizes the cholesterol-rich VLDL present in the plasma of the WHHL rabbit and that the receptor which mediates ingestion of WHHL-VLDL seems to be the same as that for beta-VLDL and leads to cholesteryl ester deposition within macrophages. Thus the uptake of the cholesterol-rich VLDL from the WHHL rabbit by macrophages in vivo may play a significant role in the pathogenesis of atherosclerosis in the WHHL rabbit.